PRESERVATION AND DEVELOPMENT OF DELI MALAY DANCE THROUGH DIGITAL TRANSFORMATION BASED ON CONTEMPORARY PERFORMANCES - Amirah, Nada; Tampubolon, Elmina; Tinambunan, Tedty Rohaya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Deli Malay dance is an important part of the cultural identity of the Medan community. However, the development of modern culture has led to a decline in interest among the younger generation and a decline in the activities of traditional arts studios. This community service activity aims to preserve and develop the Deli Malay dance through digital transformation and a contemporary approach. The program was implemented at the Sri Indera Ratu Studio through outreach, contemporary dance training, digital editing training, management mentoring, and performance publication through social media. Evaluation was conducted through pre- and post-tests, observation of participant activities, and monitoring of digital indicator achievements. Results showed an increase in participant skills, namely digital editing (from 7.70 to 9.05) and arts management and organization (from 6.15 to 8.25). Contemporary performances were successfully implemented with video documentation and digital publication. Younger participants expressed interest in participating in follow-up activities, and the studio's social media accounts demonstrated increased public engagement. In conclusion, digital transformation is an effective strategy for preserving traditional arts, increasing youth participation, and empowering the arts community. This activity has the potential to have a social and economic impact on the sustainability of the Sri Indera Ratu Studio and can be replicated at other studios in North Sumatra.